Backyard Dogs - Robert Boris; Bree, Turner; Dale Evans; Jesse Hernandez; Kaori Taylor; Robert 'Bo' Cooper; Roger Fan; Scott Hamm (USA Lions Gate, 2000)
No choreography, no protective gear, just hardcore fighting where steel folding chairs and baseball bats wrapped in barbed wire are all part of the fight. Follow three underdogs as they fight their way to the top. The Backyard Dogs are coming and all hell is about to break loose!
Two teenage boys aspire to win a backyard wrestling championship and a chance to appear on a national TV show.
Robert Boris
Language(s): English, Turkish Subtitle(s): No Subtitle
Keywords: Action; Drama